MODELING AS AN APPROACH TO PANDEMIC UNCERTAINTY MANAGEMENT: MORTALITY ASSESSMENT OF THE COVID-19 PANDEMIC: Assessment of the COVID-19 Global and Local Effects - Stevanovic, Aleksandar; Šantrić Milićević, Milena (Srpski medicinski časopis Lekarske komore, 2021)
The progression of the coronavirus disease (COVID-19) pandemic has urged medical and scientific community to attempt to model and predict the transmission of SARS-CoV-2. Forecasting possible course of the COVID-19 pandemic helped to better understand the nuanced effects of the adopted policy measures and directed us towards the future actions which might need to be undertaken. In this article, we briefly summarize few selected projection approaches used for estimating COVID-19 effects globally and locally (Serbia).
Keywords: covid-19; public health; pandemics; forecasting; transmission; risk assessment